The Influence of Work Environment and Workload on Employee Performance at the Academy of Secretarial and Management (ASM) Kencana Bandung - Deri Anggi Setiawan; Siti Sumiati; Siti Nurhayati (Journal Informatic, Education and Management (JIEM), 2026)
The main problem in this research is to determine the extent of the influence of work environment and workload on employee performance at the Academy of Secretarial and Management (ASM) Kencana Bandung. The purpose of this research is to identify and analyze the influence of work environment and workload on employee performance, as well as the magnitude of the influence of work environment and workload on employee performance at the Academy of Secretarial and Management (ASM) Kencana Bandung, both simultaneously and partially. The method used in this research is a quantitative descriptive approach. The population in this research consists of 30 employees of the Academy of Secretarial and Management (ASM) Kencana Bandung. The sample in this research is 30 employees. The data in this research is primary data, obtained from respondents’ answers to questionnaires distributed by the author. Based on the data analysis conducted by the author, the results show that the calculated F-value is 6.150 with a significance level (Sig.) of 0.000, which is smaller than 0.05 (α=5%). Therefore, it can be concluded that variables X₁ (Work Environment) and X₂ (Workload) simultaneously have a significant influence on variable Y (Performance).